DEVELOPMENT OF POLISH ORTHOGRAPHY - Лазарович, О. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the problem of evolution and becoming of Polish orthography beginning from the X-th century. As the Polish language has adopted Latin alphabet, the main problem was its adaptation to the phonetic requirements, because the medieval version of Polish language had more sounds. Polish orthography has come the long and difficult path of development.